The Escherichia coli hemL gene encodes glutamate 1-semialdehyde aminotransferase. - Ilag, L L (1991)
delta-Aminolevulinic acid (ALA), the first committed precursor of porphyrin biosynthesis, is formed in Escherichia coli by the C5 pathway in a three-step, tRNA-dependent transformation from glutamate. The first two enzymes of this pathway, glutamyl-tRNA synthetase and Glu-tRNA reductase, are known in E. coli (J. Lapointe and D. Söll, J. Biol. Chem. 247:4966-4974, 1972; D. Jahn, U. Michelsen, and D. Söll, J. Biol. Chem. 266:2542-2548, 1991). Here we present the mapping and cloning of the gene for the third enzyme, glutamate 1-semialdehyde (GSA) aminotransferase, and an initial characterization of the purified enzyme. Ethylmethane sulfonate-induced mutants of E. coli AB354 which required ALA for growth were isolated by selection for respiration-defective strains resistant to the aminoglycoside antibiotic kanamycin. Two mutations were mapped to min 4 at a locus named hemL. Map positions and resulting phenotypes suggest that hemL may be identical with the earlier described porphyrin biosynthesis mutation popC. Complementation of the auxotrophic phenotype by wild-type DNA from the corresponding clone pLC4-43 of the Clarke-Carbon bank (L. Clarke and J. Carbon, Cell 9:91-99, 1976) allowed the isolation of the gene. Physical mapping showed that hemL mapped clockwise next to fhuB. The hemL gene product was overexpressed and purified to apparent homogeneity. The pure protein efficiently converted GSA to ALA. The reaction was stimulated by the addition of pyridoxal 5' -phosphate or pyridoxamine 5' -phosphate and inhibited by gabaculine or aminooxyacetic acid. The molecular mass of the purified GSA aminotransferase under denaturing conditions was 40,000 Da, as determined by sodium dodecyl sulfate-polyacrylamide gel electrophoresis. The enzyme has apparent native molecular mass of approximately 80,000 Da, as determined by rate zonal sedimentation on glycerol gradients and molecular sieving through Superose 12, which indicates a homodimeric alpha2, structure of the protein.